Marketing Performance of Small and Medium Enterprises: Literature Study Approach with Bibliometrics - Muhammad Zainuddin; Sudarmiatin (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam (e-Journal), 2023)
The topic of marketing performance in SMEs in terms of a literature review with a Bibliometric approach has not been widely carried out. The purpose of this study is to review the extent of the topic of Marketing Performance in Small and Medium Enterprises (SMEs). Using the help of Harzing Publish or Parish and by analysing using the VOSViewer 1.6.19 application, it was found that there were 232 articles containing articles about Marketing Performance in SMEs. The results of the analysis found that topics often studied in 2020 and above are marketing performance, SMEs performance, entrepreneurial orientation, market orientation, product innovation, competitive advantage and case study. Meanwhile, countries that often conduct research on the topic of SMEs Marketing Performance are Indonesia and Nigeria.